PENGARUH MEDIA GAMBAR SERI TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR SISWA SEKOLAH DASAR: STUDI LITERATUR - Lisna Aulia; Dian Indihadi (STKIP Subang, 2026)
This study aims to examine the role of series picture media in enhancing procedural text writing skills in elementary school students through a literature study approach. The method used is qualitative descriptive with data collection techniques in the form of documentation studies from various scientific sources, such as journal articles, books, and relevant previous research findings. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that series picture media have a significant contribution in helping students understand the structure and sequence of steps in procedural texts. This media makes it easier for students to develop ideas systematically and improve their ability to arrange sentences coherently. In addition, the use of series picture media has been proven to increase students' motivation and interest in learning because it is visual and concrete, in accordance with the characteristics of elementary school students. Thus, series image media can be used as an alternative learning strategy that is effective in improving procedural text writing skills. This study recommends the optimal use of visual media in Indonesian language learning to create a more engaging and meaningful learning process.